Development of Learning Modules Using an Ethnoscience-Based Project-Based Learning Model to Enhance Students' Collaboration, Critical Reasoning, and Creativity - Fania Fitriana Rosita; Putut Marwoto; Deni Setiawan (Universitas Negeri Semarang, 2024)
The Ministry of Education, Culture, Research, and Technology emphasizes the improvement of students' character through various strategies focused on creating Pancasila Students. The main challenges at SDN Manyaran 2 include low collaboration among students and the need to improve critical and creative thinking skills. The study aims to develop, test feasibility, and evaluate the effectiveness of a Project-based Learning module based on Ethnoscience on Light and its properties for fifth-grade students, focusing on improving cooperative skills, critical reasoning, and creativity. This research follows the ADDIE development model, which includes analysis, design, development, implementation, and evaluation stages. Data collection methods include interviews, questionnaires, observation, documentation, and tests. This research was conducted in the fifth grade at SDN Manyaran 2 in Semarang, involving 28 students. The results showed that the development of the learning module was deemed highly feasible, with validation scores for media, content, and language and responses from teachers and students reaching 100%. The product's effectiveness improved students' collaboration, critical reasoning, and creativity. The research results offer students a rewarding and meaningful learning experience, encouraging their ongoing growth and learning motivation. Thus, using a learning module with Project-based Learning Based on Ethnoscience received a highly feasible validation and positively impacted enhancing students' collaboration, critical reasoning, and creativity.